THE ANALYSIS OF BEFORE AND AFTER THE PRESENCE OF MODERN RETAIL ON TRADITIONAL RETAIL IN MOTOLING - Tumewu, Claudia; Massie, James D. D.; Pandowo, Merinda H. C. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: In this era, the development of modern retail minimarkets is growing very rapidly. Not only in the urban areas, but even modern retail has reached in the rural area. This became shared challenges, to maintain local/traditional retail and small businesses, especially those that trade the same goods or services. The objective of this study is to analysis the condition of traditional retail before and after the presence of modern retail minimarkets in Motoling. This research use qualitative method with data collection techniques using in-depth interview. The sample of this study is 6 respondent. The result of this research is the presence of modern retail on traditional retail in motoling, have a negative impact because the number of visitors, sales turnover, and profit is decrease after the presence of modern retail/minimarket in motoling. Based on the result of the interview the researcher recommended the traditional retail have to improve their innovation in product, product diversity, service to the consumers, the price is same with modern retail/minimarket provide, the comfortable places, and neatness stuff.The government should limit the increasing of modern retail in rural area. Keywords: modern retail. minimarket. traditional retail, number of visitors, sales turnover, profit.